Inhibitory effects of vitamins A and C on mycelial growth and aflatoxin production by Aspergillus parasiticus - D.N. MEHTA and H.C. DUBE, R.J. VERMA, P.J. RAVAL (Indian Phytopathology, 2002)
Addition of vitamin A [retinol] or C [ascorbic acid] in SMKY liquid medium reduced aflatoxin production by A. parasiticus. At retinol concn of _1500 IU/ml mycelial growth and aflatoxin production was completely inhibited. Ascorbic acid at 10 mg/ml decreased mycelial mass by 29% and aflatoxin production by 90%. It is concluded that retinol and ascorbic acid could be safely added to food products to retard mycelial growth.